PENINGKATAN PENGETAHUAN PENGGUNAAN BAHAN TAMBAHAN PANGAN NON-NUTRITIVE SWEETENERS PADA SISWA SMPN 24 BALIKPAPAN - Arista, Yuvita Lira Vesti; Hutabarat, Michael Alexander; Ciciolini Sidabutar, Elizabeth Desfelia; Kumalaningrum, Amalia Nur (UPPM Politeknik Gorontalo, 2024)
Students often tend to consume snacks or street food without understanding the ingredients contained in the products they eat and are less selective in choosing healthy food options. This behavior can have negative consequences if the consumed products contain food additives (Bahan Tambahan Pangan, BTP) that are prohibited by regulations or exceed the permissible limits. Therefore, this community service activity aimed to enhance the knowledge of students at SMPN 24 Balikpapan regarding the use of non-nutritive sweeteners (NNS) as a type of BTP in food products, including their regulatory limits and the potential health impacts of excessive consumption. The activities consisted of field observation, socialization, mentoring, and evaluation. The socialization phase included material presentations, discussions, and the identification of food products containing NNS. Mentoring sessions introduced the types of NNS, guided the identification of products, and simulated their usage in compliance with regulatory limits. The success of the activity was evaluated through a multiple-choice test with a minimum passing grade of 60. Evaluation results indicated that the average score of the 40 participants was 76.5, and the program was considered successful, as all participants managed to complete the evaluation with a minimum score of 60. This initiative successfully enhanced students' understanding of the appropriate use of NNS in food products and raised awareness about the importance of choosing safe and healthy foods.